Population Data Centre Profile: SA NT DataLink (South Australia and Northern Territory) - Schneider, Matthias; Radbone, Christopher Gordon; Vasquez, Stacy Ann; Palfy, Miroslav; Stanley, Andrew Kristjan (International Journal of Population Data Science, 2019)
Approach Uniquely governed by a broad range of consortium partners, SA NT DataLink’s business model operates with flexibility to adapt to researcher priorities and government requirements. Its Data Linkage Unit routinely links data from over 50 sources with more than 57 million records on approximately 2.9 million individuals. It arguably provides the broadest range of linked data sources in Australia, focusing on administrative datasets and clinical registries from various health and human services domains. Operating in strict adherence with the separation principal, SA NT DataLink’s Data Integration Unit separately manages anonymised clinical and service use data in collaboration with the respective data custodians through the Custodian Controlled Data Repository, allowing approved analysts to efficiently access high quality linked anonymised data. To protect individual privacy throughout the process of data linkage and data provision, SA NT DataLink’s processes align with state, territory and federal privacy legislations. Operating consistently with National Health and Medical Research Council guidelines, linkage projects are subject to approvals by the relevant data custodians and approved Human Research Ethics Committees. Noteworthy Outputs SA NT DataLink has provided linkage services to over 160 data linkage projects, informing nationally significant research and policy initiatives, including initiatives to improve indigenous children’s hearing and child development. Conclusion To respond to a changing data linkage landscape, SA NT DataLink is continuously reviewing and improving its systems, linkage processes and governance, addressing administrative, funding, data access, social licence and data linkage challenges and opportunities to meet increasing demand and new business developments.